(untitled) (Research, Society and Development, 2022)
Expectations related to care are an important marker regarding the quality of care, the professional’s behavior, the performance of the service, based on the user’s past experiences, care needs and interpretation of the experience. The objective of this study was to evaluate the expectation and satisfaction of pregnant women with prenatal care through the application of the Brazilian version of the Patient Expectations and Satisfaction with Prenatal Care (PESPC) instrument. A cross-sectional study was carried out with 22 pregnant women attended at two basic health units. The sample calculation was performed a posteriori using the G*Power software version 3.1, obtaining an expected effect size of 0.03, alpha level of 0.05, 96% power. Descriptive analyzes were performed to characterize the sample and also to identify the response percentage regarding the items of the PESPC instrument. In order to identify the pregnant women’s satisfaction and expectations regarding prenatal care, the Fisher’s Exact Test was performed using the SPSS 20.0 Program. It was identified that there was no significant difference (p> 0.05) in the observed and expected expectation and satisfaction between the two health units. However, there was a trend in the data denoting that the pregnant women were very satisfied (86%, n=19) and with low expectations (59%, n=13). It was evident, therefore, that there was a low expectation as the pregnant women were very satisfied, although there was no statistical significance.